« Culture » dans l’œuvre de Raymond Williams - Edward Lee-Six (Contextes)
Raymond Williams writes about culture throughout his critical œuvre. But this word has several meanings in his writings, and it is by retracing its changing senses that his intellectual development can be reconstituted more generally, from Cantabrigian textual empiricism to a continental Marxism, influenced by the likes of Lukács and Goldmann. Nevertheless, however his thinking evolved, he never entirely abandoned a Cambridge English epistemology – like many of his contemporary co-founders of the cultural studies movement – and remained methodologically indebted to his starting point.